2015
DOI: 10.1016/j.snb.2014.09.109
|View full text |Cite
|
Sign up to set email alerts
|

Arrays of copper nanowire electrodes: Preparation, characterization and application as nitrate sensor

Abstract: a b s t r a c tEnsembles of copper nanowire electrodes (CuWNEEs) are prepared via electrodeposition in track-etched polycarbonate membranes. Three different preparation methods are compared showing that the better results in terms of sensor durability and reproducibility are achieved by pre-sputtering a thin gold film on the templating membrane and attaching it to a supporting electrode by exploiting the adhesion property and ionic conductivity of a thin Nafion interlayer. SEM-EDS analyses together with double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 40 publications
1
69
0
Order By: Relevance
“…In a previous study, a Zn cathode was found to have a higher electrocatalytic activity for the reduction of NO 3 − than did other cathodes. Keita found that adding Zn 2+ to the electrolyte positively affected cathodic reduction of NO 2 − , indicating that Zn is a suitable complementary cathode metal to Cu in terms of reaction kinetics. Cu catalyzed the reduction of NO 3 − to NO 2 − and Zn catalyzed the reduction of NO 2 − to the final product.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, a Zn cathode was found to have a higher electrocatalytic activity for the reduction of NO 3 − than did other cathodes. Keita found that adding Zn 2+ to the electrolyte positively affected cathodic reduction of NO 2 − , indicating that Zn is a suitable complementary cathode metal to Cu in terms of reaction kinetics. Cu catalyzed the reduction of NO 3 − to NO 2 − and Zn catalyzed the reduction of NO 2 − to the final product.…”
Section: Resultsmentioning
confidence: 99%
“…Table 5 summarises the main advantages and disadvantages of electrochemical systems. [29,30,56,66,68,72] * Less power consumption during operation [28,30] * Simple operation for direct determination of nitrate [29,30,68] *High selectivity towards targeted ions [30,56] *Fast response/feedback system [66,67] *Suitable for in situ/on line analyses [30,66] *Viable approach for portable application as relatively simple [30,56] *Low-cost system [56,68] *Small and compact system [29,30] *Surface cumulative passivation effect [28] *Complicated programmed potential protocol for renewal of microelectrode surface/electrode reactivation [28] *Extensive procedure for reagent preparation [27] *Measurement result is influenced by other contamination in analyte solution/samples [26] *Tedious reagent preparation procedure [27] *Sensitive materials such as dope polypyrrole need to be stored in the dark during polymerisation [26,29] *Sensitive materials such as dope polypyrrole are expensive [29,30] *Sensitive materials such as nitrate reductase enzymes are too sophisticated to be field-deployable [29,30] *Interference of other ions in water such as chloride, sulphate and phosphate [26] *Requirement of different types of material for the electrode in the system such as working, counter and reference electrode [27,…”
Section: And Mohd Amri MD Yunus Techniques In Advancing the Capabilimentioning
confidence: 99%
“…Many authors have studied different kinds methods to synthesize copper nanowires, including synthesis using template materials [1][2][3][4][5][6], solvothermal or hydrothermal [7,8], and wet synthesis [9][10][11][12][13]. Although the template technique produces a quite clean and straight copper nanowires, but the process requires cleaning the sacrificed materials which considered as a delicate and time-consuming process.…”
Section: Introductionmentioning
confidence: 99%
“…Although the template technique produces a quite clean and straight copper nanowires, but the process requires cleaning the sacrificed materials which considered as a delicate and time-consuming process. The solvothermal and template technique might produce a long nanowire ranging about hundred nanometers in diameter with ten micrometers in length [1][2][3][4][5][6][7][8], but the process usually took a number of hours. And therefore, it is considered as time-consuming.…”
Section: Introductionmentioning
confidence: 99%